Solar Energy: Progress and Design Concerns of Nanostructured Solar Energy Harvesting Devices (Small 19/2016). Issue 19 (11th May 2016) - Leung, Siu‐Fung; Zhang, Qianpeng; Tavakoli, Mohammad Mahdi; He, Jin; Mo, Xiaoliang; Fan, Zhiyong
Abstract : Nanoengineered materials and structures can harvest light efficiently for photovoltaic applications. Device structure design optimization and material property improvement are equally important for high performance. On page 2536, X. Mo, Z. Fan, and co‐workers summarize the design guidelines of solar energy harvesting devices to assist with a better understanding of device physics.